Video Games Impact Lifestyle Behaviors in Adults. Issue 2 (April 2016) - Cemelli, Christine Marie; Burris, Jennifer; Woolf, Kathleen
Abstract : Video games are a popular pastime for adolescents and adults worldwide. This study examined the association between video game playing (online [ONG] and offline [OFG]) and lifestyle behaviors in adults, with nongamers as controls. Participants (n = 292) completed an online survey focused on lifestyle behaviors. ONG players spent more time each week in sedentary behaviors than nongamers ( P = .005). ONG and OFG players consumed more soft drinks than nongamers ( P = .0015); ONG players reported higher energy consumption (kcal) from sugar-sweetened beverages than nongamers ( P = .012). Nongamers reported more low-fat eating behaviors than ONG players ( P = .007). This popular pastime influences overall health and further research is needed.